2016
DOI: 10.1371/journal.pone.0162816
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Diffusion-Weighted MRI on the Definition of Gross Tumor Volume in Radiotherapy of Non-Small-Cell Lung Cancer

Abstract: ObjectiveThe study was designed to evaluate diffusion-weighted magnetic resonance imaging (DWI) vs. PET-CT of the thorax in the determination of gross tumor volume (GTV) in radiotherapy planning of non-small-cell lung cancer (NSCLC).Materials and MethodsEligible patients with NSCLC who were supposed to receive definitive radio(chemo)therapy were prospectively recruited. For MRI, a respiratory gated T2-weighted sequence in axial orientation and non-gated DWI (b = 0, 800, 1,400 and apparent diffusion coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Despite these advantages, the relatively low resolution of PET (compared to CT), improper registration, and motion blurring have been recognized as limitations for contouring. MRI provides excellent soft tissue contrast, and higher image resolution than PET, but has seen limited use in target definition for lung cancer radiotherapy [19]. Hence, radiation oncologists have generally less experience with MRI than CT for target definition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite these advantages, the relatively low resolution of PET (compared to CT), improper registration, and motion blurring have been recognized as limitations for contouring. MRI provides excellent soft tissue contrast, and higher image resolution than PET, but has seen limited use in target definition for lung cancer radiotherapy [19]. Hence, radiation oncologists have generally less experience with MRI than CT for target definition.…”
Section: Discussionmentioning
confidence: 99%
“…within atelectatic lung). Variations in the apparent diffusion of water molecules due to different tissue cellularity provide contrast between tumor and the surrounding tissues in DW-MRI images and ADC maps [19]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though their study examined normal tissue structures rather than tumor volumes, they reported a mean mHD of 1.7 mm, similar to our findings (26). Fleckenstein et al compared lung cancer tumor volumes delineated on diffusion-weighted MRI registered to tumor volumes delineated using PET/CT and report a similar “average” Hausdorff distance of 2.25 mm (27). Furthermore, Commandeur et al investigated prostate volumes delineated on MRI vs. CT and report a Hausdorff distance of around 3 mm (28).…”
Section: Discussionmentioning
confidence: 99%
“…Recently published studies already pointed out the bene t of DWI in chest MRI for differential diagnosis of pulmonary nodules [10] as well as for initial staging of lung cancer and evaluation of lymph node status in particular [11,12]. Furthermore, a study group could already show a good correspondance of initial tumor volume determination when comparing PET-CT and DWI [13]. However, there is only limited data about the value of DWI in the followup assessment of NSCLC after radiochemotherapy.…”
Section: Introductionmentioning
confidence: 99%